**Answer:**

18.2

**Step-by-step explanation:**

45.5/2.5 = 18.2

F = y - h/a

aF = y - h

aF + h = y

Answer:

A) ((x+1)^2)-3

B) f(x) = 2(x+1)^2 is vertically stretched upwards by a factor of 2. In addition to this, it’s minimum value remains on the x-axis, due to there being no vertical translation like in the equation on part A.

So: The equation in part A has no vertical stretch, and does have a vertical translation, however it retains the same horizontal translation.

Explanation:

You can see the transformations by looking at the vertex and at least 1 other point.

Since it is a parabola we can start by saying:

f(x) = x^2

We also see a vertical translation of 3 units down:

f(x) = (x^2)-3

Lastly, we see a horizontal translation of 1 unit to the left:

f(x) = ((x-1)^2)-3

I believe it is transitive

**Answer:**

10,000

**Step-by-step explanation:**

The link capacity is 10^9 bps; the link usage is 10^5 bps per user, so the number of users that can be supported is ...

(10^9 bps)/(10^5 bps/user) = **10^4 users**